Interleukin 1β inhibition contributes to the antinociceptive effects of voluntary exercise on ischemia/reperfusion-induced hypersensitivity. Issue 2 (February 2018) - Ross, Jessica L.; Queme, Luis F.; Lamb, Jordan E.; Green, Kathryn J.; Ford, Zachary K.; Jankowski, Michael P.
Abstract : Abstract: Issues of peripheral circulation have been increasingly suggested as an underlying cause of musculoskeletal pain in many conditions, including sickle cell anemia and peripheral vascular disease. We have previously shown in our model of transient ischemia and reperfusion (I/R) injury of the forelimb that individual group III and IV muscle afferents display altered chemosensitivity and mechanical thresholds 1 day after injury. Functional alterations corresponded to increased evoked and spontaneous pain-related behaviors and decreased muscle strength and voluntary activity—all actions that echo clinical symptoms of ischemic myalgia. These behavioral and physiological changes appeared to originate in part from the action of increased interleukin 1β (IL1β) in the injured muscles at its upregulated IL1 receptor 1 within the dorsal root ganglion. Here, we describe that two days of voluntary wheel running prior to I/R blocks both injury-induced IL1β enhancement and the subsequent development of ischemic myalgia-like behaviors. Furthermore, the protective effects of 2 days prior exercise on the I/R-evoked increases in pain-related behaviors were also paralleled with systemic injection of the IL1 receptor antagonist during I/R. Interleukin 1 receptor antagonist treatment additionally prevented the I/R-induced changes in mechanical and chemical sensitivity of individual primary muscle afferents. Altogether, these data strengthen the evidence that transient I/R injury sensitizes group III and IV muscle afferents via increased IL1β in the muscles to stimulate ischemic myalgia development. Targeting IL1β may, therefore, be an effective treatment strategy for this insidious type of muscle pain. Abstract : Supplemental Digital Content is Available in the Text.Interleukin 1β contributes to myalgia and is modulated by exercise. Targeting this cytokine pharmacologically or through voluntary exercise ameliorates pain-related behaviors associated with ischemic muscle injury.